The dispersability of the Kronecker cover of the product of complete graphs and cycles - Shao, Zeling; Cui, Yaqin; Li, Zhiguo (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2024)
The Kronecker cover of a graph G is the Kronecker product of G and K2. The matching book embedding of a graph G is an embedding of G with the vertices on the spine, each edge within a single page so that the edges on each page do not intersect and the degree of vertices on each page is at most one. The matching book thickness of G is the minimum number of pages in a matching book embeddding of G and it denoted by mbt(G). A graph G is dispersable if mbt(G)=Δ(G), nearly dispersable if mbt(G)=Δ(G)+1. In this paper, the dispersability of the Kronecker cover of the Cartesian product of complete graphs Kp and cycles Cq is determined.